Treatment of Vitreous Hemorrhage due to Proliferative Diabetic Retinopathy in Cipto Mangunkusumo Hospital During Pandemic Era (March 2020 - March 2022): Oral Presentation - Observational Study - Resident - RAHAYU, TSANIA RACHMAH; Andayani, Gitalisa (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesProliferative diabetic retinopathy (PDR) is the most common etiology for vitreous hemorrhage (VH)and can be sight-threatening. Current treatment modalities for VH in PDR included anti-VEGFinjection, panretinal photocoagulation (PRP) laser, and vitrectomy. We conducted study to evaluatetreatment modalities and outcomes of VH in PDR during the pandemic era. MethodsA retrospective study of VH in PDR was conducted at Cipto Mangunkusumo Hospital, Indonesia,from March 2020 to March 2022. Primary treatment was the therapy planned at the initial visit,while secondary treatment was subsequent treatment after follow-ups. Good anatomical outcomewas defined as vitreous clearing at last follow-up, while functional outcome was visual acuity (VA)improvement in LogMAR. ResultsThis study included 83 patients (97 eyes), which is smaller than the previous study in our centerbefore the pandemic. Mean age was 54,28±8,57 years, with almost equal males and females. InitialVA was LogMAR 2,48 (0,15 – 2,80). The most frequent treatment for VH in PDR was vitrectomy(53,5%), followed by anti-VEGF injection, PRP laser, and observation. Glaucoma after vitrectomy wasthe most common complication (5,2%). Vitreous clearing was achieved in 85,5% of cases, which wassignificantly associated with vitrectomy surgery (p=0,013) and initial treatment time (p=0,023). TheVA improvement was LogMAR -0,48(-2,48–2,40) which was related to initial VA (p<0.05), yet therewas no significant association with treatment modality. ConclusionVitrectomy is essential to achieve vitreous clearing in VH caused by PDR. Initial visual acuity, notthe type of treatment modality, is a significant factor in vision improvement.